Absorption of food-derived balenine and its constituent amino acids in human plasma after ingestion of opah muscle and muscle extract in water - Yasutaka Shigemura; Yu Iwasaki; Megumi Hosokawa; Yurika Arai; Takuya Seko; Ryo Sawada; Yasunosuke Kawabata; Kenji Ishihara (Journal of Functional Foods)
Opah muscle is one of the abundant biological sources of balenine (Bal), which together with carnosine (Car) and anserine (Ans), is among the most widely studied of vertebrate imidazole dipeptides. The characteristics of imidazole dipeptides have been extensively investigated. We examined changes in the concentration of Bal and its constituent amino acids in human plasma following the ingestion of opah muscle extract and opah flesh. Bal plasma concentrations increased after ingestion, with maximum plasma concentrations (Cmax) of 89.87, 152.13, and 81.82 nmol/mL observed after ingestion of 5 and 10 g of opah muscle extract and 80 g of opah flesh, respectively. The constituent amino acids of Bal, 3-methyl-histidine (3-Me-His) and β-alanine (β-Ala), increased in plasma after ingestion. The Cmax of Bal was the highest of any food-derived peptide in human plasma reported to date. The findings showed that ingestion of opah muscle and muscle extract may be beneficial for human health.